LACTATE DEHYDROGENASE (LDH) SELAMA PENYIMPANAN - Teguh Triyono; Umi Solekhah Intansari; Caesar Haryo Bimoseno (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2013)
During storage, erythrocytes suffered from biomechanical alterations called the “storage lesion”, which may caused hemolysis. The hemolysis released LDH into the plasma. The LDH that was released during hemolysis made it an adequate instrument to assess the quality of in vitro blood products. The aims of this study were to analyse the alteration of LDH level at day 1, 3, 7, 14, and 28 in the WB and PRC, to analyse the correlation between LDH level with storage duration, and also to analyse enhancement differences of LDH level between WB and PRC.This research was an observational study with a cross-sectional design. As the samples there were 11 bags of WB and 10 bags of PRC. Blood products were kept in bloodbank with the temperature range of 2–6° C. The LDH level was measured with the Beckman Chemistry Analyzer. There were statistically significant alterations of LDH level started from day 7 of storage in both blood products (p<0.05). The significant strong correlation between LDH level with the storage duration were found r=0.772; r=0.835 (p<0.05) in WB and PRC respectively. The enhancement differences were found to be higher and significant in the PRC than in the WB started from day 7 of storage (p<0.05). As conclusion, LDH in WB and PRC were signifantly increased during storage, and correlate with storage duration.